The influence of business groups on board composition in offshore financial multinational enterprises. Issue 3 (June 2023) - Hearn, Bruce; Oxelheim, Lars; Randøy, Trond
Abstract: Based on resource dependence theory we argue for an influence of business groups (BGs) on the board composition of constituent offshore financial multinational enterprises (FMNEs). Using a unique sample of 171 Caribbean FMNEs in an inter-island BG setting, we find BGs' control in constituent firms to be indicative of the importance of the internal financing and intermediation within the group network. This control leads to a higher proportion of lawyers hired to the boards of directors in BG-constituent firms and supports the argument that lawyers provide skills in complex offshore regulatory frameworks that facilitate BGs' optimal tax management. Furthermore, we observe that an increased adoption of shareholder rights governance by BG-constituent firms is associated with increased engagement with outside resource providers, increased potential conflicts of interest and hence a need for hiring more lawyers. Our interpretation is that offshore FMNEs have a need for more lawyers, whose legal skill is critical to the competitive advantage of FMNEs. Highlights: Increase BG control over constituent firms implies their elevated importance in internal financing which necessitates improved tax management Increased need for competencies in offshore tax management underscores need for lawyer-directors with skills in offshore legal jurisdictions BG adoption of shareholder rights leads to increased need for lawyers as director to mitigate potential conflicts of interest BG constituent firms that are also offshore financial MNEs need more lawyer-directors for their skills to define their competitive advantages Offshore financial MNEs are associated with opaquer governance and more lawyer-directors so as to attain legitimacy with client audiences